'Power with' and 'power to' in environmental politics and the transition to sustainability. Issue 2 (4th March 2017) - Partzsch, Lena
ABSTRACT: Scholars of environmental politics demand serious reform of international governance and institutions to protect planet Earth. There is therefore an urgent need to discuss what causes change and gridlock in environmental politics. Serious reform is inextricably tied up with questions of power. The diversity with which studies on environmental politics understand power is exposed through three ideal type concepts: power with (learning and cooperation), power to (resistance and empowerment) and power over (coercion and manipulation). So far, scholars have mainly used analysis of coercive power ( over ) to explain gridlock in environmental politics; also needed is explicit acknowledgement of coaction and individual agency that can enable transition to more sustainable societies.